Perspectives on athlete-centred coaching - Pill, Shane (Routledge, Taylor & Francis Group, 2018)
Underpinned by a philosophy of empowerment, athlete-centred approaches to coaching are defined by a style that promotes learning through ownership, responsibility, initiative and awareness. Perspectives on Athlete-Centred Coaching offers an in-depth theoretical examination of player-focused coaching models, and provides professional guidance for practising coaches. Perspectives on Athlete-Centred Coaching is important reading for any students and lecturers of sports coaching or physical education, and practising coaches across any sport.